Reducing Fungal Exposure Critical for Treating Rhinosinusitis with or without Polyps [Response to Letter] - Bachert C; Bhattacharyya N; Desrosiers M; Khan AH (Journal of Asthma and Allergy, 2021)
Claus Bachert, 1, 2 Neil Bhattacharyya, 3 Martin Desrosiers, 4 Asif H Khan 1, 5 1Upper Airways Research Laboratory, Department of Otorhinolaryngology, Ghent University, Ghent, Belgium; 2CLINTEC, Karolinska Institutet, Stockholm, Sweden; 3Department of Otolaryngology, Harvard Medical School, Boston, MA, USA; 4Centre De Recherche Du Centre Hospitalier De l’Université De Montréal (CRCHUM), Montreal, QC, Canada; 5Sanofi, Chilly–Mazarin, FranceCorrespondence: Claus Bachert Email claus.bachert@ugent.be We thank Dr Curtis for his interest in our article, 1 and welcome the opportunity to address the putative role of molds and fungi in chronic rhinosinusitis (CRS).The potential contribution of fungi to the pathophysiology of CRS has been a focus of investigation many years back, and showed strong variation depending on the environment and climate. 2,3 The emerging understanding that the nose and sinuses naturally host a microbiome including viruses, bacteria, and fungi, suggests that the presence of microorganisms is itself not a key etiological factor in CRS. 4 Moreover, there is a lack of convincing immunological data to link fungi to the disease process in the great majority of CRS cases. 5 Consistent with this understanding, a 2018 Cochrane Review found no good evidence that oral or topical antifungals have a positive effect of quality of life, symptoms, or signs of disease in patients with CRS.6 Indeed, consensus guidelines advise against the use of antifungals in CRS. 4 This is in response to the Letter to the Editor View the original paper by Bachert and colleagues